Social Representations and Teaching Identity: a case study in teacher education in the social sciences at UFRN - Elda Silva do Nascimento Melo; Karla Michelle de Oliveira (Universidade Federal de Santa Catarina, 2017)
The current presence of sociology in Brazilian basic education is a new element for the subjects involved in the field including students in the teacher accreditation course in the social sciences at the Federal University at Rio Grande do Norte (UFRN). To understand how the elements learned during initial teacher education influences the construction of identity, the social representations these subjects construct about the teaching identity was studied to understand how they represent sociology teachers. To do so, we compared the elements of the central core of social representations of freshmen undergraduates and student teachers in the UFRN course. The theory of social representations and a structural approach were used as theoretical support and the free association of words technique as a methodological resource. The data analysis indicated that memory plays a crucial role in representational and identity construction, as familiarity with the discipline of sociology in high school brought new and important elements to the composition of the profile of the current freshmen in the teacher accreditation course studied.the profile of the current freshmen in bachelor investigated.